Matematyka
Wercia2511
2017-06-24 18:53:39
Witam, proszę o rozwiązanie zadania 9 -a,b,c,d pozdrawiam. Treść w załączniku ;)
Odpowiedź
Artur11052010
2017-06-24 21:49:27

[latex]mathrm{(a) frac{4}{ sqrt{3} -1} =frac{4}{ sqrt{3} -1} cdot frac{sqrt{3} +1}{ sqrt{3} +1}= frac{4sqrt{3}+4}{3-1}=frac{4sqrt{3}+4}{2}= 2+2 sqrt{3} } \ \ mathrm{(b) frac{2}{2- sqrt{3}}= frac{2}{2- sqrt{3}} cdot frac{2+ sqrt{3}}{2+ sqrt{3}} = frac{4+2 sqrt{3}}{4-3} = frac{4+2 sqrt{3}}{1}=4+2 sqrt{3} } [/latex] [latex]mathrm{(c) frac{2}{2 sqrt{3}-4} = frac{2}{2 sqrt{3}-4} cdot frac{2 sqrt{3}+4}{2 sqrt{3}+4} = frac{4 sqrt{3}+8}{12-16}= frac{4sqrt{3}+8}{-4}=-2-sqrt{3} } \ \ mathrm{(d) frac{2sqrt{3}}{sqrt{3}+1}= frac{2sqrt{3}}{sqrt{3}+1} cdot frac{sqrt{3}-1}{sqrt{3}-1}= frac{6-2sqrt{3}}{3-1}= frac{6-2sqrt{3}}{2}=3-sqrt{3} }[/latex]

kamiloww
2017-06-24 21:50:42

a)   4 / (√3 - 1) * (√3+1) / (√3+1)=        4√3+4 / 3 -1 =4√3+4 / 2=2√3+2 b)   2 /( 2 - √3 )* (2+√3) / (2+√3) =       4+2√3 / 4-3 =4+2√3 c)   2 / (2√3 - 4) * (2√3+4) / (2√3+4) =        4√3+8 / 12-16 =        4√3+8 / - 4=        √3+2 / -1 = -√3-2 d)   2√3 / (√3+1) * (√3-1) / (√3-1) =        6-2√3 /3-1=        6-2√3 / 2=3-√3

Dodaj swoją odpowiedź